Renal Mucormycosis: Post-COVID-19 Infection Presenting as Unilateral Hydronephrosis in a Young Immunocompetent Male. (21st July 2022) - Nepali, Rabin; Shrivastav, Shreya; Singh Shah, Dibya
Abstract : Mucormycosis is a rare invasive fungal infection with a high mortality rate caused by members of the family Mucoraceae. It mainly affects immunocompromised hosts such as poorly controlled diabetes mellitus, previous solid organ transplant, high-dose steroids, and hematologic malignancy. The most common sites of the disease are rhinocerebral, the skin, the lungs, and the gastrointestinal tract. In this era of COVID-19 infection, there has been a significant rise in invasive mucormycosis predominantly reported from southeast. We present a case of isolated renal mucormycosis in an apparently healthy individual with post-COVID-19 infection presenting as unilateral hydronephrosis. Timely identifying at-risk populations and having a high degree of suspicion with involvement of multidisciplinary teams are of utmost importance to diagnose and treat a rare and fatal infection. Even if there is a long history, antifungal drugs and removal of the source can result in a good outcome.